Multiple Skill Laboratory Activities: How to Improve Students’ Scientific Communication and Collaboration Skills - Malik, A.; Ubaidillah, M. (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to analyze the effects of experiment models and gender on scientific communication and collaboration skills. This study employed a quasi-experimental design consisting of five groups as control classes and five groups as experimental classes. The subject of this study was 327 students (168 students used HOT Lab and 159 used Multiple Skill; 69 Male and 258 Female from 18 to 22 years old) with heterogeneous skills and learning habits from five different universities representing four regions: Sumatra, Java, Kalimantan, and Sulawesi. The control class conducted activities based on the Higher-order Thinking Laboratory model, while the experimental class conducted activities based on the Multiple Skill Laboratory Activity Model. The data were collected by employing a validated instrument and were analyzed by employing a Multivariate test. This study shows that the experimental model has more significant influences on improving students' skills than gender. Specifically, the Multiple Skill Laboratory Activity Model (MSLAM) improves students’ collaboration skills better than communication skills. MSLAM explores more activities to practice collaboration skills, e.g., brainstorming, exploration, and measurement, while the activities for practicing communication skills is depended on analysis and presentation only. This study also reveals that the experiment model and gender are not suitable for concurrent analysis. This study is expected to provide methods for further researchers to optimize students’ scientific communication and collaboration skills. Furthermore, this study provides an overview for teachers to practice several thinking skills at one time.